Top lesson from COVID for solar geoengineering: Anticipatory research is needed - Jinnah, Sikina; Long, Jane C. S. (Frontiers in Climate, 2022)
Both COVID and climate change present existential crises that disrupt society at a global scale, cause vast and unevenly distributed human suffering along lines of race, geography, and class, and demand innovative, interdisciplinary, and international action to address. Although we deeply hope governments will address climate change through emission reductions and adaptation, we worry governments may fail to do this in time. Like vaccine research that anticipated a global pandemic, this perspective article argues that anticipatory research into possible “emergency” response measures such as solar geoengineering is needed to increase knowledge and thus confidence in any future decisions to either deploy or reject these technologies.